2006
DOI: 10.1590/s0101-20612006000200029
|View full text |Cite
|
Sign up to set email alerts
|

Potencial da variedade Joaquina para o processamento de suco clarificado e vinho seco de maçã

Abstract: A produção brasileira de maçã está voltada para o atendimento da demanda interna de fruta in natura, com uma capacidade instalada que atinge 1 milhão de toneladas por ano. Entretanto, devido à alternância de produção, fenômeno fisiológico de frutas de clima temperado, este valor pode diminuir entre 20 a 25% de uma safra para outra, como ocorreu nas de 2003/2004 e 2004/2005, com produção de 973.300 e 759.600 t, respectivamente, fato este que afeta diretamente a quantidade de maçãs comerciais e as destinadas ao … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
3
0
5
Order By: Relevance
“…A relative descriptor, namely ratio, a function of the total reducing sugar and total malic acid contents, ratio [r = f (TRS, MAL)], was left together due to its utilization in the first step of apple characterization. Czelusniak et al (2003) analyzed fruits harvested in a commercial orchard including fruits from producer and pollinator trees during the 2001/2002 season. Among 27 apple juices, one was classified as sweet; 14 as bittersweet within the boundaries of this experiment; three were found to contain more phenolic compounds; and ten were categorized as bitter sharp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A relative descriptor, namely ratio, a function of the total reducing sugar and total malic acid contents, ratio [r = f (TRS, MAL)], was left together due to its utilization in the first step of apple characterization. Czelusniak et al (2003) analyzed fruits harvested in a commercial orchard including fruits from producer and pollinator trees during the 2001/2002 season. Among 27 apple juices, one was classified as sweet; 14 as bittersweet within the boundaries of this experiment; three were found to contain more phenolic compounds; and ten were categorized as bitter sharp.…”
Section: Methodsmentioning
confidence: 99%
“…According to these criteria, Paganini et al (2004), qualified five apples as bittersweet and two as sweet from seven commercial apple varieties harvested in the 2003/2004 season. Fertonani et al (2006) reported that the samples of 'Gala' , 'Fuji' and 'Joaquina' they used to extract pectin from pomaceae were indeed qualified as bitter. Nogueira et al (2006) reported that from 14 samples of apple juices, comprising four commercial and ten advanced selections, five were qualified as bitter sharp and could be used as raw material and the others as bittersweet, obviously table apples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…De acordo com a literatura [18][19][20] 25 respectivamente. Para aqueles produtores que ainda não se enquadraram à legislação, tem-se reavaliado as condições higiênico-sanitárias das instalações, equipamentos, utensílios e manipuladores relacionados com a produção do fermentado.…”
Section: Acidez Volátilunclassified
“…23 Além disto, alguns produtores desta região ainda inserem em suas práticas de produção de fermentado adicionar aguardente ao Na literatura, encontraram-se resultados de teor alcoólico para fermentados de frutas tropicais inferiores a 10 °GL, limite míni-mo para vinhos de mesa, estabelecido pela legislação. 6 É o caso dos fermentados de maçã, 25 ata e mangaba. 26 Ao se comparar os resultados com a legislação específica para fermentados de fruta, entretanto, as amostras apresentam-se de acordo com o padrão legal.…”
Section: Teor Alcoólicounclassified